Efficacy, Pharmacokinetics, and Biodistribution of Thermosensitive Chitosan/β-Glycerophosphate Hydrogel Loaded with Docetaxel - Li, Cuiyun (Springer US, 2014)
Docetaxel (DTX) is a widely used anticancer drug for various solid tumors. However, its poor solubility in water and lack of specification are two limitations for clinical use. The aim of the study was to develop a thermosensitive chitosan/β-glycerophosphate (C/GP) hydrogel loaded with DTX for intratumoral delivery. The in vitro release profiles, in vivo antitumor efficacy, pharmacokinetics, and biodistribution of DTX-loaded C/GP hydrogel (DTX-C/GP) were evaluated. The results of in vitro release study demonstrated that DTX-C/GP had the property of controlled delivery for a reasonable time span of 3 weeks and the release period was substantially affected by initial DTX strength. The antitumor efficacy of DTX-C/GP was observed at 20 mg/kg in H22 tumor-bearing mice. It was found that the tumor volume was definitely minimized by intratumoral injection of DTX-C/GP. Compared with saline group, the tumor inhibition rate of blank gel, intravenous DTX solution, intratumoral DTX solution, and DTX-C/GP was 2.3%, 29.8%, 41.9%, and 58.1%, respectively. Further, the in vivo pharmacokinetic characteristics of DTX-C/GP correlated well with the in vitro release. DTX-C/GP significantly prolonged the DTX retention and maintained a high DTX concentration in tumor. The amount of DTX distributed to the normal tissues was minimized so that the toxicity was effectively reduced. In conclusion, DTX-C/GP demonstrated controlled release and significant efficacy and exhibited potential for further clinical development.